The “Badanti” Social Phenomenon in Lazio and Molise Regions and the Implication of Romanian Women - Șerban, Ionuș (European Scientific Journal, ESJ, 2017)
The social phenomenon of “BADANTI” is referring to a parallel social work system developed in Italy by a large number of Romanian emigrants, especially women, through their day to day jobs, mostly unqualified and often illegally. The present paper focuses on the research of the “Badanti” phenomenon especially in Lazio and Molise regions where the largest number of Romanian emigrants can be found. For example, in Lazio region the Romanian nationals represent the largest number of emigrants, approximately 40% of the total emigrants while in Molise region the Romanian emigrants represent approximately 38% of the total emigrant population. The Romanian women are part of the parallel social work system as unqualified workers by taking care of children and the elderly mostly in private homes. Although well appreciated for a job well done by their employers, who are mostly private persons, the state social work system will soon enter into a crisis because of the “Badanti”. Actions should be taken in order to preserve the welfare state and avoid the collapse of a national social work system witch could lead to grater implications in a society that can’t afford to relay on emigrants to constitute an illegal and parallel social work system. The sociological research regarding the “Badanti” phenomenon took place in the two Italian regions between April and November 2016 using questionnaires and interviews as methods of research.